Roles of DNA topoisomerases in simian virus 40 DNA replication in vitro. - Yang, L (1987)
We examined the roles of DNA topoisomerases in the replication of simian virus 40 (SV40) DNA in a cell-free system composed of an extract from HeLa cells supplemented with purified SV40 tumor antigen. When the activities of both topoisomerase I (EC 5.99.1.2) and topoisomerase II (EC 5.99.1.3) in the extract were blocked with specific inhibitors or antibodies, DNA synthesis was decreased by a factor of 15-20. Addition of purified HeLa DNA topoisomerase II to extracts immunologically depleted of both topoisomerases completely restored replication, and the replication products consisted largely of monomeric daughter molecules. Addition of purified HeLa DNA topoisomerase I to depleted extracts restored DNA synthesis, but the primary products were multiply intertwined, catenated daughter molecules. We conclude that DNA topoisomerases have at least two roles in the replication of SV40 DNA. Either topoisomerase I or topoisomerase II is sufficient to provide the unlinking activity necessary for fork propagation during SV40 DNA replication. However, topoisomerase II is uniquely required for the segregation of newly synthesized daughter molecules.